(untitled) - Hellens, Liisa Von (Hersley, PA, 2004)
The book brings together recent qualitative research studies in enterprise-wide implementations. The collection is useful as a teaching case for academia, a student reference and also for academics, researchers and IT practitioners who wish to gain a broad view of ERP implementation success and failure, The book provides relevant methodologies and recent empirical research findings in the area and includes sufficient background information for an understanding of each case but focuses on providing a rich description of more than a dozen real life cases.
Keywords: Production management,Management information systems,Business planning